Implementation of Obfuscation Technique on PHP Source Code - Maskur Maskur; Zamah Sari; Ahmad Miftakh (IAES Indonesia Section, 2018)
Source code on web based applications can be altered easily. This occurred because the source code is not compiled into an executable file. Hence, it can be read and copied easily, or be changed without permission from the author. Obfuscation is a technique that commonly used to secure the source code in any websites based application. Obfuscation is a technique to randomize the source code that make the code harder to read but still runnable, but this make the running time increased and the application will run slower then it supposed to. This increased time caused by reverse obfuscation proses to bring back the source code into originally form before interpreted by web server. This studi intended to create an obfuscation technique that keeping the application run time performance as not obfuscated called Wanna Crypt. The methods to create this applications are (1) system design using UML, (2) implementation of the system, which is done by coding or writing scripts using PHP, HTML, JavaScript, CSS to build Wanna Crypt based website, (3) Blackbox and Whitebox testing to compare the execution time. From the tests, it can be concluded that web applications using Wanna Crypt provide a longer response time than web applications without using obfuscation.